MICAI 2008 : advances in artificial intelligence : 7th Mexican International Conference on Artificial Intelligence, Atizapán de Zaragoza, Mexico, October 27-31, 2008 : proceedings - Gelbukh, Alexander (Springer, 2017)
This book constitutes the refereed proceedings of the 6th Mexican International Conference on Artificial Intelligence, MICAI 2008, held in Atizapán de Zaragoza, Mexico, in October 2008.